2017
DOI: 10.1177/0963721416689563
|View full text |Cite
|
Sign up to set email alerts
|

Where Health and Death Intersect

Abstract: This paper offers an integrative understanding of the intersection between “health” and “death” from the perspective of the terror management health model. After highlighting the potential for health-related situations to elicit concerns about mortality, we turn to the question, how do thoughts of death influence health decision-making? Across varied health domains, the answer depends on whether these cognitions are in conscious awareness or not. When mortality concerns are conscious, people engage in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Terror Management Theory (TMT) argues that people engage in predictable psychological coping mechanisms when mortality is salient, i.e., when people are aware that death is inevitable and can happen at any time (Becker, 1973;Greenberg et al, 1986). Existing research finds that highlighting the potential for death or harm in oneself and others will push people to adopt healthier attitudes and behaviors when the trigger (in our case: COVID-19) is consciously linked with the threat of death or bodily harm (e.g., Arndt and Goldenberg, 2017;Haglin et al, 2019).…”
Section: Overcoming Vaccine Hesitancy Through Effective Health Communication How Personal Economic and Collective Health Risk Frames Coulmentioning
confidence: 99%
“…Terror Management Theory (TMT) argues that people engage in predictable psychological coping mechanisms when mortality is salient, i.e., when people are aware that death is inevitable and can happen at any time (Becker, 1973;Greenberg et al, 1986). Existing research finds that highlighting the potential for death or harm in oneself and others will push people to adopt healthier attitudes and behaviors when the trigger (in our case: COVID-19) is consciously linked with the threat of death or bodily harm (e.g., Arndt and Goldenberg, 2017;Haglin et al, 2019).…”
Section: Overcoming Vaccine Hesitancy Through Effective Health Communication How Personal Economic and Collective Health Risk Frames Coulmentioning
confidence: 99%
“…The greater awareness of the terror of death and the resulting defensive dynamics help people face the difficulties that arise from mortal situations and help others relate to people who are suffering from a personal loss (12). Moreover, literature has also shown that reflecting on death and human vulnerability can also help to reduce anxiety and to better manage information related to the preservation of one's health (13). For example, a qualitative study of community death education in which participants were offered a death education course and were later asked to imagine they were affected by Amyotrophic Lateral Sclerosis (ALS) and had to prepare their Advanced Treatment Directives (ATDs) highlighted how reflecting upon the themes of the knowledge of having to die, palliative care and ATDs significantly helped participants to think to their death in a less distressful way and to be able to plan their future healthcare treatments and fundamental desires with less anxiety (14).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate this meta-theoretical application of evolutionary psychology, consider the terror management approach to health motivation (Arndt & Goldenberg, 2017;Goldenberg & Arndt, 2008). This model proposes that many health behaviors are motivated by existential anxieties, an assumption that is critically tied to a consideration of evolution theory.…”
Section: Evolutionary Psychology Provides a Meta-theory Of Health Behmentioning
confidence: 99%
“…Specifically, the model maintains that 'the fear of death itself ultimately serves the instinct for self-preservation, […] a very basic and primitive psychological adaptation that functions to perpetuate the organism's genes' (Pyszczynski, Greenberg, & Solomon, 1997, p. 5). According to Arndt and Goldenberg (2017) the terror management health model 'offers a foundation for understanding how people manage existential insecurity as well as harnessing the effects of death-related thought to engage productive health behavior change' (Arndt & Goldenberg, 2017, p. 130).…”
Section: Evolutionary Psychology Provides a Meta-theory Of Health Behmentioning
confidence: 99%
See 1 more Smart Citation